2023
DOI: 10.3390/ijms24097816
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolic Switch of Physical Activity in Non-Obese Insulin Resistant Individuals

Abstract: Healthy non-obese insulin resistant (IR) individuals are at higher risk of metabolic syndrome. The metabolic signature of the increased risk was previously determined. Physical activity can lower the risk of insulin resistance, but the underlying metabolic pathways remain to be determined. In this study, the common and unique metabolic signatures of insulin sensitive (IS) and IR individuals in active and sedentary individuals were determined. Data from 305 young, aged 20–30, non-obese participants from Qatar b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Interestingly, 1-carboxyethylphenylalanine associated in our study with the poor responder group was identified by Wilmanski to be associated with less microbiome diversity, while methyl glucopyranoside (α+β) associated in our study with the good responders, was identified to be associated with more microbiome diversity and a healthier status. Additionally, our previous studies on QBB data from non-diabetic individuals showed that 1-carboxyethylphenylalanine was identified as the most discriminating metabolite of insulin resistance [ 35 , 36 ]. Our results suggest that dysbiosis in gut microbiota is associated with a reduced response to metformin, and improving gut health could improve the effectiveness of metformin.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, 1-carboxyethylphenylalanine associated in our study with the poor responder group was identified by Wilmanski to be associated with less microbiome diversity, while methyl glucopyranoside (α+β) associated in our study with the good responders, was identified to be associated with more microbiome diversity and a healthier status. Additionally, our previous studies on QBB data from non-diabetic individuals showed that 1-carboxyethylphenylalanine was identified as the most discriminating metabolite of insulin resistance [ 35 , 36 ]. Our results suggest that dysbiosis in gut microbiota is associated with a reduced response to metformin, and improving gut health could improve the effectiveness of metformin.…”
Section: Discussionmentioning
confidence: 99%